Adapting the deliberative democracy approach to LMIC settings: a case study in Nigeria - Gaydos, Laura M.; Salami, Kabiru; Yusuf, Wasiu; Idigbe, Ifeoma; Awolude, Olutosin; Ogunsola, Olabanjo; Staple, Tyree; Ezemelue, Priscilla; Ajayi, Oluseye; Ezechi, Oliver; McBride, Colleen M; Flowers, Lisa (Frontiers in Public Health, 2025)
BackgroundDeveloping sustainable health promotion interventions in low- and middle-income countries (LMICs) faces challenges due to limited infrastructure and diverse cultural contexts. Community engagement is essential for effective health promotion, but higher intensity strategies may be infeasible in under-resourced settings. This study aimed to adapt the Mentor Mother (MM) HIV peer program to include HPV self-screening for Nigerian women living with HIV using deliberative democracy (DD) principles.MethodsThe study utilized a tiered DD approach to explore stakeholders’ perspectives on feasible and sustainable strategies for the MM program. The process included two tiers: an initial deliberation among the research team and a subsequent community deliberation. The research team deliberation involved online sessions to identify feasible program adaptations as well as a model deliberation process. The community deliberation included a diverse group of stakeholders who participated in a two-day conference, engaging in small and large group discussions to reach consensus on program adaptations.ResultsThe research team identified two options for HPV sample collection and result delivery. The community deliberation reached consensus on both questions. For sample collection, the preferred option was for MMs to educate women in organized groups and transport samples to the laboratory. For result delivery, the consensus was for MMs to return all results to patients after additional training. The process demonstrated high levels of participant satisfaction, increased self-efficacy in explaining HPV screening, and adherence to DD principles of inclusivity, reasoned justification, and societal perspective.ConclusionThe DD process was feasible and effective in adapting the MM program for HPV screening in Nigeria. The approach empowered community members and enhanced the intervention’s development. However, adaptations were necessary to address cultural norms and logistical challenges. The study highlights the potential of DD to inform health promotion strategies in LMICs, ensuring interventions are culturally appropriate and sustainable.